Analysis of Mixed Effects Model for Randomized Block Designs with Both-sided Neighbor-Effects - Sapam, Sobita; Sinha, Bikas Kumar (International Journal of Statistical Sciences, 2023)
In this study we confine our attention to Randomized Block Designs (RBDs) with random block effects in the presence of both-sided neighbor-effects and focus our attention to (i) estimation of variance components, and (ii) estimation of treatment contrasts as well as both left-sided and right sided neighbor-effects contrasts. We start with a simple set-up of 4 blocks and 4 treatments in an RBD. This we do by concurrently studying three distinct RBDs with the same parameters. However, the allocations of Left Neighbor (LN)- and Right Neighbor (RN)-Effects are assumed to be different across the RBDs. International Journal of Statistical Sciences, Vol. 23(2), November, 2023, pp 19-30